Phase II Study to Evaluate the Safety and Efficacy of the Oral Neurokinin-1 Receptor Antagonist Casopitant (GW679769) Administered with Ondansetron for the Prevention of Postoperative and Postdischarge Nausea and Vomiting in High-risk Patients - Singla, Neil K.; Singla, Sonia K.; Chung, Frances; Kutsogiannis, Demetrios J.; Blackburn, Linda; Lane, Stephen R.; Levin, Jeremey; Johnson, Brendan; Pergolizzi, Joseph V. (Anesthesiology (Philadelphia), 2010)
In recent years, there has been an increased interest in using a multimodal approach with combined agents to treat postoperative nausea and vomiting. This study evaluated whether the addition of an oral dose of the neurokinin-1 receptor antagonist casopitant improved the antiemetic efficacy of an intravenous dose of ondansetron hydrochloride. The authors enrolled 702 premenopausal or perimenopausal, nonsmoking, female patients aged 18-55 yr with a history of postoperative nausea and vomiting and/or motion sickness undergoing a laparoscopic or laparotomic gynecologic surgical procedure or laparoscopic cholecystectomy with general anesthesia. Subjects were randomized to one of five treatment arms: standard ondansetron 4 mg with casopitant at 0, 50, 100, or 150 mg, or 0 mg ondansetron with casopitant at 150 mg (the latter arm was considered an exploratory study group and was included in the safety analysis but not in the efficacy analysis). A significantly greater proportion of patients in all of the active casopitant plus ondansetron groups achieved a complete response (i.e., no vomiting, retching, rescue medication, or premature withdrawal) during the first 24 h postoperatively versus those in the ondansetron-alone group (59-62% vs. 40%, respectively; P = 0.0006). All active doses seemed to be well tolerated; headache, dizziness, and constipation were the most frequently reported adverse events. Compared with ondansetron alone, the casopitant and ondansetron combination results in superior emesis prevention during the first 24 h postoperatively in female patients with known risk factors for postoperative nausea and vomiting.